Krisis Literasi di Sekolah: Sebuah Refleksi Pedagogis Calon Guru - Josua Silalahi; Bobby Pramjit Singh; Agnes Silalahi; Glora Sitinjak; Tia Siahaan; Lastri Sitompul; Melda Sihombing; Anggun Sinurat; Kesmy Simanjuntak (Yayasan Bayt Shufiya Nusantara, 2026)
This study explores the dialectic between the basic literacy crisis and the pedagogical challenges faced by pre-service teachers during the Teaching Practicum Program (PPL) in a rural junior high school setting. Utilizing a narrative-reflective approach, the research reveals a profound disconnection between formal curricular demands and the cognitive realities of seventh-grade students experiencing absolute literacy barriers. This phenomenon is not merely a technical failure in reading but a manifestation of the deficit of cultural capital within the domestic sphere, compounded by the dominance of instructional methods that are non-adaptive to student characteristics. The findings indicate that while students face severe textual literacy obstacles, they possess significant agency and holistic potential in kinetic-organizational activities. Interventions through direct practice-based multisensory strategies proved capable of reconstructing student responsiveness and comprehension, while renegotiating the role of novice teachers amidst structural constraints. This study recommends a reorientation of the PPL curriculum to be more sensitive to rural sociological contexts and emphasizes the strengthening of collaboration between educational institutions and the social environment to break the cycle of functional illiteracy in secondary education.